Risk Factors for Sporadic Infection With Campylobacter Spp. Among Children in Israel: A Case–control Study. Issue 3 (March 2016) - Bassal, Ravit; Ovadia, Adi; Bromberg, Michal; Stein, Michal; Shainberg, Bracha; Loewenthal, Shulamit; Somekh, Eli; Cohen, Daniel; Shohat, Tamy
Abstract : Background: Campylobacter spp. has been identified as one of the leading causes of bacterial gastroenteritis in the world. In recent years, an increase in the incidence of campylobacteriosis in several countries, including Israel, was demonstrated. The incidence rate of campylobacteriosis in Israel increased from 22.3 per 100, 000 in 1997 to 77.4 per 100, 000 in 2009. The aim of this study was to explore risk factors for sporadic infection with Campylobacter among young children in Israel. Methods: A matched case–control study was performed to investigate risk factors for sporadic Campylobacter infection among 113 affected children of 1–5 years of age and 113 age-matched, gender-matched and neighborhood-matched controls. Information about exposure to potential risk factors was obtained via telephone interview and was evaluated by conditional logistic regression analysis. Results: In the multivariable model, for each additional chicken meal consumed during the week before the onset of illness, the odds for Campylobacter infection increased by 32% [adjusted matched odds ratios (aMOR): 1.32; 95% confidence interval (CI): 1.01–1.72; P = 0.04], whereas consumption of fruits and vegetables decreased the odds for Campylobacter infection by 97% (aMOR: 0.03; 95% CI: 0.00–0.28; P < 0.01), and for each additional child living in the household, the odds for infection decreased by 48% (aMOR: 0.52; 95% CI: 0.33–0.83; P < 0.01). Using diaper increased the odds for campylobacteriosis (aMOR: 7.36; 95% CI: 1.66–32.70; P < 0.01). Conclusions: Interventions that focus on proper handling of chicken and chicken products, hand washing and encouraging consumption of fruits and vegetables could help in controlling Campylobacter infections.